Pneumomediastinum: A Rare Presentation of Inflicted Injuries in Infants - Bajinting, Adam; Lee, Adam; Lunneen, Abby; Fitzpatrick, Colleen M.; Villalona, Gustavo A. (Journal of Pediatric Intensive Care, 2020)
Reports of incidental pneumomediastinum in infants secondary to inflicted trauma are limited. A retrospective review of infants with pneumomediastinum and history of inflicted trauma was performed. A comprehensive literature review was performed. Three infants presented with pneumomediastinum associated with inflicted trauma. Mean age was 4.6 weeks. All patients underwent diagnostic studies, as well as a standardized evaluation for nonaccidental trauma. All patients with pneumomediastinum were resolved at follow-up. Review of the literature identified other cases with similar presentations with related oropharyngeal injuries. Spontaneous pneumomediastinum in previously healthy infants may be associated with inflicted injuries. Clinicians should be aware of the possibility of an oropharyngeal perforation related to this presentation.
Keywords: emergency; pneumomediastinum; non-accidental trauma